Development of new smart metal nanomaterials based on titanium-dioxide for photocatalytic and antimicrobial activities - Kuburović, Nataša D.; Golubović, Aleksandar V.; Babinčev, Ljiljana M. (Vojnotehnički glasnik / Military Technical Courier, 2018)
The subject of this study was the synthesis, characterization and testing of titanium (IV) oxide nanoparticles (TiO2-NPs) and their lanthanum (La3+), iron (Fe3+) and vanadium (V3+) dopants for the photocatalytic and microbiological activity, as well as their comparison with the catalytic activity of the tested commercial TiO2 (Degussa P-25® and anatase nanoparticles, 99.9 %, Alfa Aesar Lancaster). The TiO2-NPs photocatalysts  were synthetized and doped with different metal dopants concentrations for different calcination durations, such as: TiO2-NPs (anatase-NPs, calcination duration of 5 and 7 h), La3+ (0.65, 1, 2, 3, 4, 5 and 6 wt. %, calcination duration of 7 h), Fe3+ (1, 2.5, 3.0 and 5 wt. %, calcination duration of 7 and 24 h), and V3+ (10 wt. %, calcination duration of 7 and 24 h). The Pseudomonas aeruginosa strains DV 2739 and ATCC 9023 were used as model microorganisms in the microbiological experiments performed in a microbiological cabinet. The photocatalytic and coupled photocatalytic-microbiological processes were performed in a slurry-catalyst bath circulation photoreactor in the presence of direct UV radiation simulated with a sodium lamp SONT UV400 in lab conditions. The study has demonstrated that the catalyst sample S28, an La-dopant with a concentration of 1wt. %, displays the best photocatalytic properties among all La-dopants, while the best photocatalytic activity among all catalysts was achieved in S111 sample, an Fe-dopant of titania (5 wt. %, calcination duration of 7 h). Our results also show different degradation rates for TiO2 doped with V3+ of 10.0 wt. %, samples S93 and S96, synthetized with different duration times (7h and 24h, respectively) and calcination heating rates (66.7 and 135 ᵒC/h, respectively), which can be explained by anomalies in their behavior. Finally, the best antimicrobial activity is obtained in S24 sample, an Fe-dopant for which it was shown that 0.25 mg/L could be toxic for microorganisms. In accordance with our results of superior Fe-dopant characteristics and theoretical knowledge for TiO2 nanoparticles doped with Ag, Au and Fe, we get directions for further studies of their photocatalytic and antimicrobial activities, as well as for the development of TiO2-nanoparticles and nanotubes for enhancing antibiotics and their use in cancer treatment.
Keywords: titanium-dioxide; TiO2-nanoparticles; TiO2 doped with La3; Fe3 and V3; calcination duration; Pseudomonas aeruginosa strains DV 2739 and ATCC 9023; photocatalytic activity; antimicrobial activity